Performance of healthy subjects on an ecologically valid test for social cognition: The short, Dutch Version of The Awareness of Social Inference Test (TASIT) - Westerhof-Evers, Herma J.; Visser-Keizer, Annemarie C.; McDonald, Skye; Spikman, Jacoba M. (Journal of clinical and experimental neuropsychology, 2014)
The present paper addresses the psychometric quality of the shortened Dutch version of The Awareness of Social Inference Test (TASIT), a social cognition task comprising dynamic social interactions. Because the original TASIT required a rather long administration time, two shortened parallel forms were developed. Results showed that TASIT-short was feasible and that the two alternate forms were reasonably comparable in a group of neurologically healthy individuals (N = 98). Also, the results confirmed the ecological validity of TASIT-short in this healthy group. The test appeared sensitive to brain injury as it differentiated between the healthy subjects and a group of patients with acquired brain injury (N = 16). On the basis of the present study we conclude that TASIT-short has added value to the assessment of social cognition in patients with acquired brain injury.